2022
DOI: 10.3389/fimmu.2022.895519
|View full text |Cite
|
Sign up to set email alerts
|

As in Real Estate, Location Matters: Cellular Expression of Complement Varies Between Macular and Peripheral Regions of the Retina and Supporting Tissues

Abstract: The cellular events that dictate the initiation of the complement pathway in ocular degeneration, such as age-related macular degeneration (AMD), is poorly understood. Using gene expression analysis (single cell and bulk), mass spectrometry, and immunohistochemistry, we dissected the role of multiple retinal and choroidal cell types in determining the complement homeostasis. Our scRNA-seq data show that the cellular response to early AMD is more robust in the choroid, particularly in fibroblasts, pericytes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 98 publications
(112 reference statements)
0
21
0
Order By: Relevance
“…A combination of transcriptomics and proteomics was employed by Zauhar et al [ 58 ], to dissect the role of multiple retinal and choroidal cell types (Müller glia, neurons and RPE/choroid) in determining complement homeostasis. The results indicated that this process has a key role in the involvement of RPE cells in progression to late AMD.…”
Section: Resultsmentioning
confidence: 99%
“…A combination of transcriptomics and proteomics was employed by Zauhar et al [ 58 ], to dissect the role of multiple retinal and choroidal cell types (Müller glia, neurons and RPE/choroid) in determining complement homeostasis. The results indicated that this process has a key role in the involvement of RPE cells in progression to late AMD.…”
Section: Resultsmentioning
confidence: 99%
“…When treating the RPE cell line Acute Retinal Pigment Epithelium‐19 (ARPE‐19) with WT C9 and the p.Pro167Ser variant, however, no differences were detected 65 . In this context, it should be noted that RPE do not secrete C9, but show high concentrations of the C9 inhibitor CD59 50,51 . However, as discussed in the following, multiple studies showed susceptibility of the choroid to C5b‐9 deposition.…”
Section: The Alternative Pathway In Amdmentioning
confidence: 97%
“…This study involved 11 samples of human macula from three dataset series (GSE137537, GSE188280, and GSE203499) (Menon et al, 2019;Zauhar et al, 2022), including retinas from four AMD patients and seven healthy controls without degeneration. The details of each donor were listed in Table 1.…”
Section: Human Samples Of Retinal Macula For Analysismentioning
confidence: 99%